2016
DOI: 10.1080/19648189.2016.1271361
|View full text |Cite
|
Sign up to set email alerts
|

An elastic-viscoplastic model for saturated frozen soils

Abstract: From the material science point of view, saturated frozen soil is a natural particulate composite, composed of solid grains, ice and unfrozen water. The mechanical behaviour of such a material is strongly affected by the amount of ice. The amount of ice depends on the temperature and the applied mechanical stresses. The influence of ice content and temperature on the mechanical behaviour and the coupling effects on the reverse direction can be mentioned as the main difference between frozen and unfrozen soils.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The prepared earth samples were placed in a conservation box at a temperature of 25 ± 2 °C and 50% relative humidity and maintained to the appropriate age. Conduct the corresponding tests and record the test data according to <Standard for Soil Test Methods GBT 50123-201933> 36 .
Figure 3 Soil specimens preparation instrument.
…”
Section: Test Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prepared earth samples were placed in a conservation box at a temperature of 25 ± 2 °C and 50% relative humidity and maintained to the appropriate age. Conduct the corresponding tests and record the test data according to <Standard for Soil Test Methods GBT 50123-201933> 36 .
Figure 3 Soil specimens preparation instrument.
…”
Section: Test Materials and Methodsmentioning
confidence: 99%
“…Chang et al 33 pointed out that the Xanthan gum has a better reinforcement effect on well graded soil, and the reinforcement effect mainly depends on four factors: soil type, xanthan gum content, curing age, and mixing method. The results of Ahmadi et al [34][35][36] showed that the cleaning improver such as xanthan gum can significantly improve the mechanical properties of soil after dry-wet cycle (W-D) and freeze-thaw cycle (F-T). Kumar et al 24 confirmed that the Xanthan gum is more efficient in reducing soil permeability compared to guar gum and pectin.…”
Section: Openmentioning
confidence: 99%
“…On the other hand, the mean and deviatoric stress-induced pore pressure development at high UWC condition can play important roles in mechanical and hydrological analyses of frozen saline soil [13,31], and an effective stress model with the consideration of pore pressure can be a better option for thermo-hydro-mechanical modeling than a total stress model. However, the study of load-induced pore pressure development for frozen soil is quite scarce, although pore-water pressure in frozen soil has been measured for other kinds of investigation, such as freezing and thawing tests [15,18,54], cryogenic suction at the water-ice interface [19,30], and water redistribution in one dimensional freezing process [40,56,57].…”
Section: Introductionmentioning
confidence: 99%
“…This process triggers the creation of new cracks, the expansion of existing cracks, and a reduction in slope strength (Kjelstrup et al, 2021;. This degradation compromises the mechanical integrity of rocks in geological engineering, threatening the safety and stability of infrastructures in cold regions (Ghoreishian Amiri et al, 2022). The expansion of pores and microcracks in rocks leads to a greater water storage capacity, intensifying frost damage upon subsequent freezing (Zhang et al, 2020).…”
mentioning
confidence: 99%